Understanding social situations: study protocol for a randomized controlled trial evaluating a novel social cognitive training versus modified problem-solving training for people with psychosis - Fiszdon, Joanna M.; Bell, Morris D.; Fulford, Daniel; Roberts, David L.; Dziura, James; Parente, Lori; Nasse, Alexis; Choi, Jimmy (Frontiers in Psychiatry, 2024)
Background: Psychotic spectrum disorders (PSD) are associated with poor social function. In this study, we investigate which of two different types of 2-month long training courses is more effective in improving day-to-day interactions and quality of life. Methods/Design: Participants with psychotic spectrum disorders will be randomly assigned to one of two training courses. Social functioning, everyday activities, social cognition and symptoms will be assessed at multiple timepoints, including baseline, treatment midpoint, end of treatment and 2-month follow-up. One training focuses on how to make good judgments about what other people may be thinking or feeling in social situations, and why people might act in certain ways in different situations. The other training focuses on different strategies for handling everyday problems and stressors. Both trainings are done in one-on-one sessions with a research staff member. There will be 16-20 training sessions, each about 45-60 minutes long. The investigators will ask participants to attend 2 training sessions per week, so the total training time should be about 2 months. Clinical Trials Registration: NCT04557124